Privacy, intrusion detection, and response : technologies for protecting networks - Kabiri, Peyman , 1968- (Hershey, Pennsylvania : Information Science Reference, 2012)
"This book discusses the latest trends and developments in network security and privacy, and serves as a vital reference for researchers, academics, and practitioners working in the field of privacy, intrusion detection, and response"--Provided by publisher
1. A structured approach to selecting data collection mechanisms for intrusion detection -- 2. Protecting enterprise networks: An intrusion detection technique based on auto-reclosing -- 3. Usage of broadcast messaging in a distributed hash table for intrusion detection -- 4. An entropy-based architecture for intrusion detection in LAN traffic -- 5. Botnet behavior detection using network synchronism -- 6. Detecting denial of service attacks on SIP based services and proposing solutions -- 7. Dimension reduction and its effects on clustering for intrusion detection -- 8. A subspace-based analysis method for anomaly detection in large and high-dimensional network connection data streams -- 9. Applying weighted PCA on multiclass classification for intrusion detection
"Premier reference source"--Cover
Includes bibliographical references and index
Keywords: Computer network -- Security measures